Analisis Aspek Pasar sebagai Pilar Utama dalam Studi Kelayakan Bisnis untuk Mendukung Keberlanjutan Usaha - Adinda Khairunisa Ahmadi; Dina Fakhira; Nabila Intan Sahfira; Reza Novriansah Siahaan; Nadila Syahputri; Mutiah Khaira Sihotang (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The market aspect plays a strategic role in business feasibility studies, serving as a fundamental basis for assessing the potential success of a business. This study aims to analyze market aspects, including demand potential, segmentation, competition, and consumer behavior, as the primary pillar to support business sustainability. This research employs a qualitative method based on literature studies by reviewing various sources such as scholarly journals, industry reports, and other relevant documents. The findings indicate that understanding market dynamics provides substantial competitive advantages, particularly in designing marketing strategies responsive to consumer needs and market changes. The literature analysis also highlights that business success heavily depends on the ability of business actors to comprehend market trends, anticipate competition, and effectively leverage opportunities. These findings have significant implications in assisting business practitioners, investors, and policymakers in developing data-driven business strategies that support long-term sustainability. This study emphasizes the importance of market aspects as a fundamental element in every business feasibility study, focusing not only on profitability but also on business resilience amidst complex market dynamics.